Aquisição de discriminações auditivo-táteis e emergência de leitura recombinativa em Braille - Quinteiro, Regiane de Souza (2016)
Reading is a complex ability that involves a set of discriminated operants. In exposure to discrimination teaching with printed words the elements are combined and recombined in new words that control how to read the new words (recombinative reading). The present study had the objective of investigating whether previous discoveries on recombinative reading with tactile stimuli from the Braille alphabet were replicable. It was investigated the acquisition of pseudowords printed in Braille and the combination and recombination of the textual units in recombinative reading. Four literate adults with acquired visual impairment learned auditory-tactile conditional discriminations between dictated and printed pseudowords in Roman alphabet (AB) and between dictated and printed pseudowords in Braille (AC). Periodic tests evaluated new choice relations (BC, CB, AC) and oral textual responding (CD) with taught and new words. Two experimental studies (with two sets of words) were conducted, they were composed of six teachingtesting cycles (two words in each cycle) with tactile stimuli with font size 90 (Study 1) and size 40 (Study 2). The pseudowords were created to strengthen recombinative reading: four vowels and four consonants composed 4 syllables and formed 12 dissyllable words for teaching and 14 words for tests (each syllable was presented in the first and last position of the words at the same times). The four participants learned all conditional discriminations and formed equivalence classes that included dictated and tactile words in the two modalities. All of them showed scores higher than 80% in the selection of the new words. New words Braille reading showed variability: two participants showed correct responses with scores higher than 75%; the others showed between 41 and 79%. The results replicated and expanding the previous discoveries about to Braille stimuli and their elemental control by within-syllable units can develop recombinative reading. Teaching procedure variables, stimuli modalities, and the elements overlapping in different words had an important role to generate Braille reading.